Kompleksitas Model Sekolah Adaptif di Masa Pandemi Dalam Mengelola Pembiayaan - Nurochim Nurochim; Siti Ngaisah Nurochim (Universitas Muhammadiyah Surakarta, 2021)
The pandemic is a challenge for school organizations. One of challenge is financial management. The purpose of this study is to describe the innovations in school management in a pandemic. This study uses literature review to obtain an overview of school institutions to adapt. Data was collected through previous studies that discussed schools, funding, school components, external conditions of schools, and pandemics. The results show that schools are institutionally composed of people who have different goals, skills, cultural capital, but schools have a goal of achieving educational goals. During this pandemic, schools have challenges in managing funding, many parents as sources of funding cannot pay school fees. However, schools adapt to existing conditions, but also schools as complex institutions. Innovations made by school managers by analyzing elements such as formation, adjustment, complex social systems, and actors. The innovation made by schools is to adjust budgets and income effectively and efficiently.